Impact of subsystems on the overall system availability for the large scale grid-connected photovoltaic systems. (April 2020) - Sayed, A.; EL-Shimy, M.; El-Metwally, M.; Elshahed, M.
Highlights: This paper presents a complete RAM analysis for large scale solar-PV systems. Total subsystem availability and overall availability of the PV system are estimated. Availability importance measures for large-scale PV power plants are presented. Critical subsystems with priority for the PV system are revealed using these measures. Improving the overall availability of the solar-PV systems is also presented. Abstract: This paper demonstrates the impact of subsystem availability on a large scale grid-connected photovoltaic (PV) systems' performance. Subsystem denotes to the installation of some subassemblies, which can be very small or gigantic in size, that serve this subsystem and the overall system. The analysis is largely based on a huge worldwide dataset of failures and repairs of various subassemblies, derived from different large scale grid-connected solar-PV systems. Major subsystems, such as a photovoltaic inverters (PVI), are also included, which are shown to have a significant impact for improving on the overall system availability. An improved reliability block diagram (RBD) with an exponential probability distribution function is presented for estimating the reliability and availability performance of seven practical grid-connected solar-PV systems. In addition, availability importance measures are employed to rank various subsystems with regards to their impact on the overall system availability. Accordingly, it will be helping in identifying the subsystems that the planned maintenance should focus on in order to achieve the desired level of the availability. The secure operation of the system will be achieved by this approach. The implementation demonstrates the efficiency and the effectiveness of the proposed approach which may significantly contribute to enhancing the system availability.